Diseño de una agencia de viajes en el desarrollo del turismo de aventura en la ciudad de Manta - Martínez Lucas, Andrés Enrique (2014)
This research aimed at the realization tube design a travel agency in the development of adventure tourism in the city of Manta, for this he proceeded to use the steps, methods and techniques that help in the research process. The development of this paper consists of 4 phases; in the first phase of the project general data project name is detailed, coverage, location, sector and project type, in the second step is performed is presented and the diagnosis problem, where the current situation is described Manta, identifies and diagnoses the problem, and then establish the baseline where social, demographic, economic, environmental and tourism issues are discussed canton. In the third phase the objectives of both the overall project and specific, posed and then make the logical framework matrix. The fourth phase is feasibility and sustainability plan, which is part of the technical feasibility where physical and technical characteristics of the materials and supplies that make up the project, in which the operating structure of the travel agency establishes detailed the distribution of positions, functions and be shaped as different organizational areas of the company, in turn describes the economic and financial viability in this are identified, quantified and assessed expenses, costs and benefits that the project will generate.